OPTIMASI NILAI RESISTANSI PADA RANGKAIAN RESISTANSI KOMBINASI PARALEL-SERI YANG SETARA DENGAN NILAI RESISTANSI RUSAK MENGGUNAKAN ALGORITMA GENETIKA - F.X. Wisnu Yudo Untoro (Institut Teknologi Nasional Yogyakarta, 2019)
This paper discusses the limited availability of resistance values used to obtain the resistance value of a damaged resistor. The proposal offered is to use a parallel-series combination resistance circuit form. To obtain the resistance values for a series of parallel-series combination resistor in order to produce a resistance value equivalent to the resistance value of the damaged resistor using a genetic algorithm. The simulation results show that by providing input in the form of resistance value of the damaged resistor of 75 á¿¼, population number 10, number of generations of 50, as well as by input of genetic algorithm operators, between a 90% crossover probability, and 10% gene mutation probability an equivalent resistance value is obtained with the resistance value of the damaged resistor for the parallel-series combination resistance circuit being R1= 50 á¿¼, R2 = 50 á¿¼, and R3 = 50 á¿¼..